(4,4′)-Bipyridine in vacuo and in solvents: a quantum chemical study of a prototypical floppy molecule from a molecular transport perspective - Bâldea, Ioan; Köppel, Horst; Wenzel, Wolfgang (Physical chemistry, chemical physics, 2013)
We report results of quantum chemical calculations for the neutral and anionic species of (4,4′)-bipyridine (44BPY), a prototypical molecule with a floppy degree of freedom, placed in vacuo and in solvents. In addition to equilibrium geometries and vibrational frequencies and spectra, we present adiabatic energy curves for the vibrational modes with significant intramolecular reorganization upon charge transfer. Special attention is paid to the floppy strongly anharmonic degree of freedom of 44BPY, which is related to the most salient structural feature, namely the twist angle θ between the two pyridine rings. The relevance of the present results for molecular transport will be emphasized. We show that the solvent acts as a selective gate electrode and propose a scissor operator to account for solvent effects on molecular transport. Our result on the conductance G vs. cos2θ is consistent with a significant transmission in perpendicular conformation indicated by previous microscopic analysis.